2014
DOI: 10.5089/9781475515275.001
|View full text |Cite
|
Sign up to set email alerts
|

From Volatility to Stability in Expenditure: Stabilization Funds in Resource-Rich Countries

Abstract: This paper examines the effect of stabilization funds on the volatility of government expenditure in resource-rich countries. Using a panel data set of 68 resource-rich countries over 1988-2012, the results find that the existence of stabilization funds contributes to smoothing government expenditure. The spending volatility in countries that have established such funds is found to be 13 percent lower in the main estimation, and similar impacts are found in robustness tests. The analysis also shows that politi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…Note that the coe¢ cient of CT oT;it is negative and signi…cant for all lag orders, while the coe¢ cient of the interactive institutional quality term is positive and statistically signi…cant for p = 1; 2; and 3. These results are in line with Frankel et al (2013), who argue that the better institutions in developing countries are, the more likely they are to pursue less procyclical or more countercyclical …scal policy, as well as Sugawara (2014) who shows that the two signi…cant factors in reducing government expenditure volatility are stronger institutions and …scal rules. Overall, our results suggest that while volatility represents a fundamental barrier to economic prosperity, the establishment of SWFs, as well as appropriate institutions, can help mitigating the negative e¤ects.…”
Section: The Role Of Swfs and Institutional Qualitysupporting
confidence: 86%
See 1 more Smart Citation
“…Note that the coe¢ cient of CT oT;it is negative and signi…cant for all lag orders, while the coe¢ cient of the interactive institutional quality term is positive and statistically signi…cant for p = 1; 2; and 3. These results are in line with Frankel et al (2013), who argue that the better institutions in developing countries are, the more likely they are to pursue less procyclical or more countercyclical …scal policy, as well as Sugawara (2014) who shows that the two signi…cant factors in reducing government expenditure volatility are stronger institutions and …scal rules. Overall, our results suggest that while volatility represents a fundamental barrier to economic prosperity, the establishment of SWFs, as well as appropriate institutions, can help mitigating the negative e¤ects.…”
Section: The Role Of Swfs and Institutional Qualitysupporting
confidence: 86%
“…Sugawara (2014) shows that government expenditure volatility is lower in countries with stabilization funds. Koh (2016) illustrates that …scal policy becomes more counter-cyclical after the establishment of oil funds, and that these funds are typically associated with smoother government consumption.…”
Section: The Role Of Swfs and Institutional Qualitymentioning
confidence: 99%
“…Thus the establishment and the operation of a resource fund in this case might not be correlated with significant changes in governance and institutional quality. These arguments extend into the sphere of governance and institutions earlier discussion in the existing literature which supports the view that resource funds can add little in the fiscal and macroeconomic policies in countries where sound fiscal management of natural resources is in place (see for instance Ossowski, 2003 andSugawara, 2014).…”
Section: Introductionmentioning
confidence: 79%
“…The theoretical discussion on the usefulness of resource funds as tools of economic policy has challenged their effectiveness arguing that resource funds can add little in the absence of strong institutions, while they can have limited, if any, impact when strong institutions are in place. Sugawara (2014) argues that if a resource-rich country maintains sound fiscal policies and appropriate management of natural resources, the country might not need to establish a resource fund to separate the revenue and expenditure cycles. On the relationship between resource funds, governance and Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/resourpol institutions a recent study by Tsani (2013) has shown that resource funds may serve as a tool of insulating resource-rich economies against the adverse effects of resource wealth and support government effectiveness, rule of law and control of corruption in countries rich in natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the success of stabilisation funds, many studies find that they are effective fiscal instruments in resource‐rich economies (e.g. Fasano, ; Shabsigh and Ilahi, ; Bagattini, ; Sugawara, ). However, a potential factor that may hinder the effectiveness is weak institution, according to Ossowski et al .…”
Section: Stabilisation Funds and Fiscal Rules In Oil‐rich Economies: mentioning
confidence: 99%